Vivências morais e sofrimento moral de enfermeiros que cuidam de crianças com necessidades especiais de saúde - Santos, Raíssa Passos dos (2016)
Introduction: Pediatric nursing practice is becoming increasingly complex, since the profile of Brazilian children is in the process of change, bringing the increase in the number of children with special health care needs. Nurses are professionals with an important knowledge about the best interests of children and families, advocating on behalf of their welfare and are thus inclined to experience moral distress. Aim: The aim of this study was to examine the experiences of moral distress of nurses who care for children with special healthcare needs. Methodology: interpretive phenomenology was selected as the study method. Nine nurses working at three different pediatric units of a teaching hospital were interview in November and December 2014. The data analysis process was held according to Patricia Benner's framework. The process consisted of transcription, coding, thematic analysis, and search for paradigm cases and exemplars. All the ethical aspects were preserved and the study was approved by the Research Ethics Committee of the institution under number 36618114.4.0000.5346. Results: Data analysis identified three themes. The themes arises from the relationships that nurses experienced in their daily lives and therefore their different moral experiences. Their moral experiences can be changed by their engagements. The nurses of this study are engaged in different levels according to their concerns throughout pediatrics nursing practice. Depending on the relationship they are living; with the health team, with other nurses, with the child's family, and the child; the participants can experience distress, anguish, frustration, satisfaction, responsibility. Conclusion: The findings identified that the engagement of nurses can be modified all the time during childcare situations and can instigate or inhibit their moral agency, according to their understanding of the nursing practice.